Genome-wide selection signal analysis reveals the adaptability of Tibetan sheep to high altitudes - Song, Yufang; Yuan, Chao; Guo, Tingting; Chen, Bowen; Wang, Fan; Lu, Zengkui; Liu, Jianbin (Frontiers in Veterinary Science, 2025)
Altitude adaptation is a complex process involving multiple physiological and biochemical responses to hypoxia and other environmental stresses. In-depth genetic analysis of Tibetan sheep, which exhibit significant adaptations to high-altitude hypoxia, promises to elucidate hypoxia-tolerance mechanisms in plateau animals. Here, we conducted a genome-wide selection scan on three Tibetan sheep populations: low-altitude Tao (TS; 2887 m), medium-altitude Tianjun white (WT; 3331 m), and high-altitude Huoerba (HB; 4614 m). Using the population differentiation index (Fst) and nucleotide diversity (θπ) ratio, we analyzed selection signals associated with hypoxia at high-altitudes. We screened 865, 941, and 876 candidate genes in the TS vs. WT, TS vs. HB, and WT vs. HB group comparisons, respectively, 55 of which were jointly screened. Integrated analysis further identified several key pathways and genes under positive selection in Tibetan sheep populations, including metabolic pathways (GSTA1, ALAS1, HMOX2, SCD, ME1, ACSL6, PIK3C2G), melanogenesis (MITF, EP300), and the HIF-1 signaling pathway (ERBB2, HIF1A, RELA). Among these, the metabolic pathways may enhance energy production under hypoxic conditions, while melanogenesis and the HIF-1 signaling pathway are likely associated with ultraviolet radiation protection and hypoxia tolerance, respectively. This study provides valuable insights into the genetic mechanism of high-altitude adaptation in Tibetan sheep, and also provides important theoretical basis for the conservation and breeding of Tibetan sheep and the sustainable development of plateau animal husbandry.